Discontinuist and continuist approaches of language evolution… and beyond - Lise Habib-Dassetto; Alban Lemasson; Cristel Portes; Marie Montant (Revue de Primatologie)
Language, according to classical philosophy, is considered as the expression of thought specific to human. This function is still considered qualitatively different from the rest of animal communication in several fields such as psychology, neuroscience or cognitive science, leading to numerous debates in the scientific community. Many comparative studies have been conducted during the past century, with the aim of revealing the structure, function and evolution of language’s components, opposing a discontinuist vision to a continuist vision of this evolution. This article aims at proposing an integrative approach of the comparison between human and non-human primates’ communication systems that goes beyond the opposition between discontinuism and continuism. We propose to encourage inter-specific comparisons of communication systems using the point of view of biology that, contrary to the discontinuist position and its quest for human uniqueness, study similarities between species (even non-human) rather than differences. Several works belonging to the continuist approach have shown that some characteristics of language can be found in non-human primates, such as social learning, functional referential communication or even forms of combinatoriality. Nevertheless, by using human language as the one and only frame of reference, these studies might miss some general communicative features that many primates have in common. We propose to enrich the conception of communication systems by considering them as comparable flexible interactional systems that produce a variety of combined multimodal signals, whose organization is strongly shaped by the environmental and social constraints.